Distribution of ABO blood groups in beta thalassemia patients dependent on blood transfusion In Bagdad city - Sarah M. Mahmoud Marbut; Maha A. Hamdi; Abdulhadi M.Jumaa; Basma Abbas Salman (Journal of Madenat Alelem University College, 2018)
Introduction: People have different blood types, known as blood groups. Antigens are hereditary determined and plays a vital role in transfusion safety. The discovery of the ABO blood groups by Karl Land steiner was an important achievement in the history of blood transfusion followed by discovery of Rh antigen. There are differences in the distribution of ABO, and Rh (D) blood groups amongst different populations. The study of blood groups plays an important role in various genetic studies, in clinical studies for reliable geographical information and in blood transfusion practice, which will help in reducing morbidity and mortality rate. The aim of the study is to find out whether there is any relationship between ABO blood groups and thalassemia patients. Methods: The present study was done at Baghdad  teaching hospital, GIT center from 1st of  Jan 2017 to the end of September  2017.  A cross sectional study was done in Baghdad-Iraq, in collaboration with GIT center. A total of 200 ß- thalassemia patients without viral hepatitis. (100 males and 100 females) (the age of patients is between 7 to 24 years). Thalassemia patients ABO type beta major were tested by ABO blood group at laboratory department. Determination of ABO blood group Blood group is determined by slide haemagglutination technique. Result: In male and female thalassemia patients, blood group O is the highest %, followed by B blood group in in males. However, the 2nd one in female patients is (A) blood group. The lowest ABO blood group in male and female patients is AB blood group. In thalassemia patients, both gender, the highest percentage rate of Rh antigen is found in O+ , (43% in males and 38% in female patients), followed by B+, (29% in males and 21% in female patients), However, and the lowest was in ABO blood group. From the present study;  it could be summarized that ABO blood groups in thalassemia patients was found mostly in O+ blood group, and almost there is no thalassemia in AB- and O- groups.